Values of serum carcinoembryonic antigen and elastase 1 in diagnosis of pancreatic carcinoma. Issue 12 (December 1984) - Tatsuta, M; Yamamura, H; Noguchi, S; Ichii, M; Iishi, H; Okuda, S
Abstract : Carcinoembryonic antigen (CEA) and elastase 1 in the serum were determined by enzyme immunoassay and radioimmunoassay, respectively, in 224 healthy subjects, 49 patients with pancreatitis, 53 patients with pancreatic carcinoma and 129 patients with cancer in other organs. The CEA concentrations in the serum were significantly higher in patients with pancreatic carcinoma than in those with pancreatitis, but this concentration was not a satisfactory indicator of pancreatic carcinoma localised to allow irradication by resection as it was raised in only 47% of the patients. High CEA concentrations were also slightly, but not significantly, more frequent in patients with cancer of the pancreatic body or tail, and unresectable cancer or cancer of more than 6.0 cm in longest diameter than in those with cancer of the pancreatic head, resectable cancer or cancer of less than 6.0 cm diameter. Serum elastase 1 was raised in only 42% of the patients with pancreatic carcinoma and could not be used to distinguish patients with pancreatic carcinoma from those with pancreatitis. In contrast with CEA, however, its concentration was abnormally high significantly more frequently in patients with cancer of less than 6.0 cm in longest diameter than in those with larger tumours. It was also raised slightly, but not significantly, more frequently in those with cancer of the pancreatic head and in patients with resectable cancer than in those with unresectable cancer. A combination of these two tests raised the diagnostic rate of pancreatic carcinoma to 77% without a remarkable decrease in the specificity for pancreatic carcinoma. In particular, it raised the diagnostic rates of cases of cancer of the pancreatic head, resectable cancer and cancers of less than 3.0 cm and 3.0-6.0 cm in longest diameter. Therefore, a combination of measurements of CEA and elastase 1 in the serum is very useful for early detection of pancreatic carcinoma.